2016
DOI: 10.18311/jnr/2016/4782
|View full text |Cite
|
Sign up to set email alerts
|

Tea Polyphenols as Natural Products for Potential Future Management of HIV Infection - an overview

Abstract: Belonging to the <em>Lentivirus</em> genus of animal retroviruses, human immunodeficiency virus (HIV) is the etiological agent of acquired immunodeficiency syndrome (AIDS) which attacks cells of the immune system including CD4<sup>+</sup> T lymphocytes, monocytes, macrophages and dendritic cells. A rapid progression to immunodeficiency and the higher transmissibility of HIV-1 compared to HIV-2 are hallmarks of the worldwide spread of AIDS. Conventional HIV treatments are limited by drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…EGCG has also been found effective against HIV-1 and inhibits viral replication by acting at various stages. It blocks interaction of gp120 with CD4 by interfering with reverse transcriptase ( Sodagari et al., 2016 ). A report suggested that EGCG inhibits the production of p24 antigen on isolated CD4 receptor cells, macrophages and CD4 ± T cells depending on its dose ( Nance et al., 2009 ).…”
Section: Antiviral Properties Of Egcgmentioning
confidence: 99%
“…EGCG has also been found effective against HIV-1 and inhibits viral replication by acting at various stages. It blocks interaction of gp120 with CD4 by interfering with reverse transcriptase ( Sodagari et al., 2016 ). A report suggested that EGCG inhibits the production of p24 antigen on isolated CD4 receptor cells, macrophages and CD4 ± T cells depending on its dose ( Nance et al., 2009 ).…”
Section: Antiviral Properties Of Egcgmentioning
confidence: 99%
“…Documented potential properties and probable mechanism of action of green tea compounds are presented in Table 1. 3C-like protease, binding to viral surface proteins [78], [80], [77], [81], [79], [82], [83], [84] Catechins Inhibiting adherention and cell penetration, disruption of the viral replication cycle, inhibiting HCV replication, anti-inflammatory, inhibiting SARS-Cov-2 main protease [85], [76], [86], [87] Quercetin Inhibiting SARS-Cov replication by inhibition of SARS-Cov-3C-like protease [88] Catechins, quercetin Inhibiting COVID-19 main protease and structural proteins [73]…”
Section: Antiviral Propertiesmentioning
confidence: 99%
“…The absorption of EGCG is relatively high, with a maximal plasma concentration of more than 1 g/ml (Zaveri, 2006 ). At micromolar concentrations, EGCG has been demonstrated to suppress infections caused by various viruses such as porcine reproductive and respiratory Syndrome Virus (PRRSV), Dengue virus, HIV‐1, and hepatitis C virus (HCV) (Calland et al, 2012 ; Ge et al, 2018 ; Raekiansyah et al, 2018 ; Sodagari et al, 2016 ). When taken orally, EGCG, on the other hand, is unstable and has a low bioavailability.…”
Section: Immunomodulatory Role Of Egcgmentioning
confidence: 99%
“…Epigallocatechin‐3‐gallate (EGCG) is the most abundant polyphenolic catechin found in Camellia sinensis (L.) Kuntz (tea plant), and its anti‐inflammatory, antiviral, and antioxidative properties are well documented (Hu et al, 2018 ; Khan et al, 2006 ; Zaveri, 2006 ). According to some reports, EGCG has antiviral activity at micromolar concentrations sufficient to inhibit the infection of viruses like herpes simplex virus, influenza A virus, and dengue virus (Calland et al, 2012 ; Ge et al, 2018 ; Sodagari et al, 2016 ), suggesting that this phytochemical could be used along with antiviral drugs to treat COVID‐19 disease.…”
Section: Introductionmentioning
confidence: 99%